The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.6007/ijarped/v12-i1/15691
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Teachers’ Assessment Literacy in Enacting Cefr-Aligned Classroom-Based Assessment in Malaysian Secondary Schools ESL Classroom

Abstract: This past five years has seen a drastic reform in the Malaysian education system. The reform prompts significant changes in teaching and learning and the assessment system. The emphasis on high-stakes examinations were revised and a new assessment system is introduced. In 2021, many high-stake examinations like Uijan Pencapaian Sekolah Rendah (UPSR) and Pentaksiran Tingkatan 3 (PT3) were abolished due to the reason of being ineffective tools to measure students' learning capability. Since the abolishment, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 14 publications
(19 reference statements)
0
0
0
Order By: Relevance
“…The reform in the assessment system has also led to changes in the practice of ESL teachers' teaching and learning process in classroom (Marzaini et al, 2023). These changes demand ESL teachers to be fully language assessment literate in order to be able to accomplish the aim of implementing CBA-aligned with CEFR effectively.…”
Section: Malaysian Esl Teachers' Language Assessment Practices In Imp...mentioning
confidence: 99%
See 4 more Smart Citations
“…The reform in the assessment system has also led to changes in the practice of ESL teachers' teaching and learning process in classroom (Marzaini et al, 2023). These changes demand ESL teachers to be fully language assessment literate in order to be able to accomplish the aim of implementing CBA-aligned with CEFR effectively.…”
Section: Malaysian Esl Teachers' Language Assessment Practices In Imp...mentioning
confidence: 99%
“…These changes demand ESL teachers to be fully language assessment literate in order to be able to accomplish the aim of implementing CBA-aligned with CEFR effectively. Ironically, Marzaini et al (2023) claimed that Malaysian ESL teachers have a low level of LAL to implement CEFR-aligned CBA in their classroom practices. The studies of Arumugham (2020); Suppian et al ( 2020) and Yusoff and Lee (2021) revealed that CBA is often implemented not in line with the objectives set.…”
Section: Malaysian Esl Teachers' Language Assessment Practices In Imp...mentioning
confidence: 99%
See 3 more Smart Citations